2013
DOI: 10.1186/1471-2105-14-127
|View full text |Cite
|
Sign up to set email alerts
|

VaccImm: simulating peptide vaccination in cancer therapy

Abstract: BackgroundDespite progress in conventional cancer therapies, cancer is still one of the leading causes of death in industrial nations. Therefore, an urgent need of progress in fighting cancer remains. A promising alternative to conventional methods is immune therapy. This relies on the fact that low-immunogenic tumours can be eradicated if an immune response against them is induced. Peptide vaccination is carried out by injecting tumour peptides into a patient to trigger a specific immune response against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It exploits immunoinformatics tools to calculate B-cell epitopes and TCR peptides of antigenic sequences, and a generic contact potential to estimate the affinity between T-cells receptors and peptides presented by antigen-presenting cells, infected cells, or, as in the present case, malignant (tumor) cells. 40 41 Besides that, the model accepts in input any pre-calculated list of peptides associated with a “ranked likelihood” to bind a certain HLA, 42 for example, NetMHCstabpan. 39 Moreover, an arbitrary value is introduced in the modeling to evaluate the conformational similarity between the paired peptides.…”
Section: Methodsmentioning
confidence: 99%
“…It exploits immunoinformatics tools to calculate B-cell epitopes and TCR peptides of antigenic sequences, and a generic contact potential to estimate the affinity between T-cells receptors and peptides presented by antigen-presenting cells, infected cells, or, as in the present case, malignant (tumor) cells. 40 41 Besides that, the model accepts in input any pre-calculated list of peptides associated with a “ranked likelihood” to bind a certain HLA, 42 for example, NetMHCstabpan. 39 Moreover, an arbitrary value is introduced in the modeling to evaluate the conformational similarity between the paired peptides.…”
Section: Methodsmentioning
confidence: 99%
“…or EBV [21], [22]), cancer immuno-prevention [23], [24], type 1 hypersensitivity [25] and the chronic inflammation associated to type 2 diabetes [26] as well as specific aspects of the immune dynamics such as lymphocytes homing in lymph nodes [27], the gene regulation leading to cell differentiation [28], clonal dominance in heterologous immune responses [29] and also vaccination-eliciting fish immunity [30]. Relevant to the present study, the model has recently being used to simulate the response to a multi-epitope vaccine against SARS-CoV-2 [31], [32].…”
Section: Virus Definitionmentioning
confidence: 99%
“…It is also observed that memory against cancer will be helpful to reduce initial phase of cancer or to destroy tumour cells. In [75], von Eichborn et al proposed an ABM, termed as VaccImm for cancer immunotherapy vaccination. Agents such as tumour antigens, immune cells, and molecules such as IL-2, antibodies with the help of their biological rules were simulated in VaccImm that models adaptive response.…”
Section: Modelling Of Immune Response To Cancermentioning
confidence: 99%